Transoral laser microsurgery for supraglottic and hypopharyngeal squamous cancers - Garg, Rishav; Aggarwal, Kushal; Sandhu, Seerat (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Open partial laryngectomies for supraglottic and hypopharyngeal cancers have a very high incidence of aspiration in the post-operative period with resultant delay in restoration of swallowing. The present study examines the functional efficacy and oncological safety of transoral laser microsurgery (TLM) for select subset of T1/T2/T3 squamous cancers of the supraglottis and hypopharynx with freely mobile vocal cords that are easily accessible on suspension microlaryngoscopy. Methods: This is a retrospective study of squamous cancers of the supraglottis and hypopharynx treated with transoral CO2 laser resection. Results: Oncologically, resections performed under the magnification of the operating microscope are safe and yield high local control rates ranging from 79% to 85% for supraglottic cancer and from 63% to 89% for hypopharyngeal cancer. Conclusions: Transoral laser microsurgery (TLM) in selected cases of supraglottis and hypopharyngeal squamous cancers is safe procedure with several advantages over the open partial laryngectomy procedures as also over radiotherapy.